2017
DOI: 10.1038/srep40557
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the molecular mechanism for the differential inhibitory activities of compounds against MTH1

Abstract: MTH1 can hydrolyze oxidized nucleotides and is required for cancer survival. The IC50 values were 0.8 nM for TH287 with a methyl substitution, 5.0 nM for TH588 with a cyclopropyl substitution, and 2.1 μM for TH650 with an oxetanyl substitution. Thus, it is very significant to understand inhibitory mechanisms of these structurally similar compounds against MTH1 and influences of the substituent on the bioactivities. Our MD researches indicate that TH287 maintains significant hydrogen bonds with Asn33 and Asp119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…By contrast, ( S )-crizotinib potently inhibited c-MET and ErbB3 phosphorylation, similar to its ( R )-enantiomer. Thus, while the MTH1-binding capacity of both drugs is not in question 8,9,15,16,19,30 , the effects on CRC cell survival do not seem to be due to inhibition of MTH1, as they are unaffected by experimental manipulation of ROS levels. Our results obtained in 3D model systems are in line with previous work in other model systems and other cancer types showing MTH1-independent anti-tumour effects of TH588 and ( S )-crizotinib 1519 .…”
Section: Discussionmentioning
confidence: 93%
“…By contrast, ( S )-crizotinib potently inhibited c-MET and ErbB3 phosphorylation, similar to its ( R )-enantiomer. Thus, while the MTH1-binding capacity of both drugs is not in question 8,9,15,16,19,30 , the effects on CRC cell survival do not seem to be due to inhibition of MTH1, as they are unaffected by experimental manipulation of ROS levels. Our results obtained in 3D model systems are in line with previous work in other model systems and other cancer types showing MTH1-independent anti-tumour effects of TH588 and ( S )-crizotinib 1519 .…”
Section: Discussionmentioning
confidence: 93%
“…While some recent articles reported that MTH1 may not be an independent anti-cancer target, [ 33 35 ] there is no doubt that MTH1 is a target of cellular antioxidative defenses [ 1 , 36 38 ]. For both normal and cancerous cells, it is not uncommon that different cells have different sensitivities to MTH1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus cancer cells with shorten telomere would be more sensitive to MTH1 inhibition and the oxidative stress [ 1 ]. The inhibition or disruption of MTH1 is sure to reduce the cell's ability to cope with oxidative stress, especially for cancer cells [ 1 4 , 36 ]. MTH1, which protects cancer cells from the oxidative-stress-induced damage of dNTP pools, is a promising target for designing effective anti-cancer drugs with low toxicities [ 1 4 , 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, targeting this enzymatic function has been proposed to induce single strand breaks and G:C to T:A transversion mutations during DNA replication [ 5 ]. The MTH1 inhibitor TH588 was identified by Gad and co-authors in 2014 [ 6 ] and has been used in several studies subsequently [ 7 9 ]. Other investigators have generated inhibitors independently as reviewed very recently [ 10 ].…”
Section: Introductionmentioning
confidence: 99%